Thakitta Tharikitta Bouncing Ball - Jacab Samson Muttada (Chennai Tulika publishers, 2011)
Thakitta tharikitta thakitta tharikitta...the pages of this simple, easy-to-read book resound with the rhythm of dancing steps. It's a fun story, but more fun is the language of dance, and how it makes a little boy jump and turn and twirl. Abu's big red ball goes bouncing, thakitta thom and then thadeem. Maybe it bounces in different notes in other places! The delightful illustrations keep step with the bouncing ball.
Grade - Sr.Kg, G - 1,2